NOMINA MAKIAN DALAM BAHASA MINANGKABAU DI TERMINAL AUA KUNIANG BUKITTINGGI - Ningsih, Sari Deswita; Agustina, Agustina; Ngusman, Ngusman (Universitas Negeri Padang, 2018)
The purpose of this study was to describe the form, context and function of invective in the language of Minangkabau in Terminal Aua Kuniang Bukittinggi. The data of study is the expressions used invective language of Minangkabau society in Terminal Aua Kuniang Bukittinggi district. The data source of this research is the speech of informants in Terminal Aua Kuniang South Bukittinggi district. The finding of study is eksplained three things, namely 1) the form of invective, 2) the context of using invective expression, and 3) the functions of using invective expressions. The form of invective consists of word and phrases. Function invective expression consists of: (1) express their resentment, (2) strong angerand extreme, (3) as comedy, (4) a means of expressing in timacy in relationships, (5) contempt, (6) expressed frustration and annoyance, and (7) as a means of disclosure as tonishment.Keywords: form, context, function, invective, Minangkabau language